Surface Enhanced Raman Scattering and Gated Materials for Sensing Applications: The Ultrasensitive Detection of Mycoplasma and Cocaine. Issue 38 (9th August 2016) - Oroval, Mar; Coronado‐Puchau, Marc; Langer, Judith; Sanz‐Ortiz, Marta Norah; Ribes, Ángela; Aznar, Elena; Coll, Carmen; Marcos, María Dolores; Sancenón, Félix; Liz‐Marzán, Luis M.; Martínez‐Máñez, Ramón
Abstract: We present herein a novel combination of gated mesoporous silica nanoparticles (MSNs) and surface‐enhanced Raman scattering (SERS) for sensing applications. As a proof‐of‐concept, we show the design of a system comprising MSNs loaded with crystal violet (CV), a molecule with high Raman cross section acting as SERS reporter, and capped with either a suitable DNA sequence for the detection of Mycoplasma genomic DNA or with an aptamer that selectively coordinates cocaine. In both cases the presence of the corresponding target analyte in solution (i.e., genomic DNA or cocaine) resulted in the release of CV. CV delivery was detected by SERS upon adsorption on gold nanotriangles (AuNTs), which display an efficient electromagnetic field enhancement and a high colloidal stability. By using this novel procedure a limit of detection of at least 30 copies DNA per μL was determined for the detection of Mycoplasma genomic DNA, whereas cocaine was detected at concentrations as low as 10 nm . Abstract : Sniffer dog : The combination of gated materials with surface enhanced Raman scattering spectroscopy for designing sensitive and selective sensing systems is presented (see figure). Crystal violet‐loaded mesoporous silica nanoparticles capped with suitable biomolecules were combined with AuNT@PEG (NT=nanotriangle, PEG=polyethyleneglycol) for the detection of Mycoplasma genomic DNA and cocaine.